Application of Phillips Curve in Indonesia (Long Term And Short Term Approach) - Sulthan Faiz Akbar (Jurnal Pendidikan Ekonomi Indonesia, 2022)
Inflation and unemployment are macroeconomic problems experienced by many countries in the world where every policymaker in every country wants these two problems to be addressed together. However, Phillips Curve Theory states that there is a reciprocal relationship between inflation and unemployment so that when economic policymakers implement a policy to increase economic income, these two problems actually have a negative relationship between the two in the short term. This study aims to examine the relationship between inflation and unemployment in Indonesia with a sample of the inflation rate and unemployment rate in Indonesia in 2006-2020 in each semester. On the other hand, this research is carried out based on the Phillips Curve Theory which is relevant in different countries but also this theory is irrelevant in different countries thus causing uncertainty of the study. The research method used is an explanatory quantitative method with documentation techniques obtained from the Central Statistics Agency. The data analysis technique in this study used the Pearson Product Moment Correlation Test method, Granger Causality Test, Cointegration Test, and Error Correction Model. The findings in this study state that inflation and unemployment in Indonesia period have a positive causality relationship between the two where the direction of causality is unemployment to inflation in the long term and based on the results of this study, the Phillips Curve Theory does not apply in Indonesia